Cardiac-Autonomic Imbalance and Baroreflex Dysfunction in the Renovascular Angiotensin-Dependent Hypertensive Mouse - Bianca P. Campagnaro; Agata L. Gava; Silvana S. Meyrelles; Elisardo C. Vasquez (International Journal of Hypertension, 2012)
Mouse models provide powerful tools for studying the mechanisms underlying the dysfunction of the autonomic reflex control of cardiovascular function and those involved in cardiovascular diseases. The established murine model of two-kidney, one-clip (2K1C) angiotensin II-dependent hypertension represents a useful tool for studying the neural control of cardiovascular function. In this paper, we discuss the main contributions from our laboratory and others regarding cardiac-autonomic imbalance and baroreflex dysfunction. We show recent data from the angiotensin-dependent hypertensive mouse demonstrating DNA damage and oxidative stress using the comet assay and flow cytometry, respectively. Finally, we highlight the relationships between angiotensin and peripheral and central nervous system areas of cardiovascular control and oxidative stress in the 2K1C hypertensive mouse.